EXPERIMENTAL AND NUMERICAL INVESTIGATIONS OF ICE CRYSTALLIZATION IN AQUEOUS SOLUTIONS - CHEGNIMONHAN, Kouamy Victorin; GUIDI, Tognon Clotide; TOUKOUROU, Chakirou Akanho; Josset, Christophe; Galimova, Larisa V; VIANOU, COKOU ANTOINE (My University, 2016)
The formation of ice slurry from pure water or different aqueous solutions of Mono Propylene Glycol (MPG) immersed in an isothermal cooling bath is studied. The mathematical model is based on the unsteady heat equation coupled with a kinetic description of crystal growth obtained from classical nucleation theory. The kinetics approach takes into account the stochastic behaviour of nucleation and includes molecules diffusion involved in crystal growth. A focus is made on the implementation of the method and its validity. The approach is suitable to describe ice growth in MPG-water binary solutions (weight concentration range wc % from 0 to 25). A correlation is proposed to address ice kinetics of crystallisation for slurries obtained from MPG solutions.
Keywords: ice slurry; crystallization; secondary refrigerant; sustainable development; energy saving; inverse method; energy storage; ice formation; nucleation; refrigeration; genetic algorithm